2002
DOI: 10.1590/s1516-93322002000400008
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo da levedura Phaffia rhodozyma (Xanthophyllomyces dendrorhous) em processo descontínuo alimentado para produção de astaxantina

Abstract: A levedura Phaffia rhodozyma, produtora de astaxantina, pigmento carotenóide largamente empregado na aqüicultura de peixes e crustáceos, pode ser eficientemente cultivada num meio de cultura de baixo custo, à base de caldo de cana diluído 1:10 e uréia a 1 g/L. No entanto, a produção de biomassa e a formação do carotenóide sofrem a inibição pelo substrato (efeito "Crabtree"), limitando desta forma a utilização do caldo de cana com concentrações da fonte de carbono superiores a 20 g/L, importante consideração na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Comparing to batch processes, using the same fermentation conditions (Moriel, 2004), a reduction in the cellular astaxanthin concentration (364.59 to 303.34 µg/g biomass) was observed, besides the increasing in the biomass (0.072 to 0.195 g/l/h) and astaxanthin productivities (0.026 to 0.059 mg/l/h). Chociai et al (2002) also observed the same reduction in the cellular astaxanthin concentration, using pulsed fed-batch processes and the same substrates. It showed that great variations in the carbohydrate concentration of the fermentation medium during the process could interfere on the astaxanthin production.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Comparing to batch processes, using the same fermentation conditions (Moriel, 2004), a reduction in the cellular astaxanthin concentration (364.59 to 303.34 µg/g biomass) was observed, besides the increasing in the biomass (0.072 to 0.195 g/l/h) and astaxanthin productivities (0.026 to 0.059 mg/l/h). Chociai et al (2002) also observed the same reduction in the cellular astaxanthin concentration, using pulsed fed-batch processes and the same substrates. It showed that great variations in the carbohydrate concentration of the fermentation medium during the process could interfere on the astaxanthin production.…”
Section: Methodssupporting
confidence: 66%
“…Since these animals can not synthesize carotenoids, pigments must be supplemented to their feeds, allowing the assimilation and providing the characteristic pigmentation of these fish, increasing the quality and consumer acceptance in the market-place (Johnson and An, 1991). Because of the increasing worldwide market, the high cost of synthetic astaxanthin and the need of astaxanthin obtained from natural sources at a low cost and high productivity, the yeast Phaffia rhodozyma has been widely used for astaxanthin production in fed-batch fermentation processes using low cost materials as substrates (An et al, 2001;Chociai et al, 2002;Vazquez et al, 1998). We studied the influence of the feeding method on the astaxanthin production by the yeast Phaffia rhodozyma in continuous and pulsed fed-batch process, using low cost materials (sugar cane juice and urea) as substrates.…”
Section: Astaxanthinmentioning
confidence: 99%
“…Carotenoids may be synthesized by plants, yeasts, molds, algae and bacteria while animals must get them from diets (Chociai et al 2002;Bhosale and Bernstein 2005). According to Oliveira et al (2009), the world production of natural carotenoids is estimated in 100 millions ton per year, which represents an income of more than one billion dollars.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increasing worldwide market, the high cost of synthetic astaxanthin and the need of astaxanthin obtained from natural sources, in scaled-up FIGURE 1 -Astaxanthin processes, at low cost and high productivity, several low cost substrates have been used as substrate for the cultivation of the yeast P. rhodozyma, like peat hydrolysate (Acheampong, Martin, 1995), wood hydrolysates (Cruz, Parajó, 1998;Parajó et al, 1997;, corn wet-milling coproducts (Hayman, Mannarelli, Leathers, 1995) and even sugar cane juice (Chociai et al, 2002). In this way, the aim of this work is to optimize the biomass and astaxanthin production by the yeast P. rhodozyma, using fed-batch fermentation processes and low cost substrates (sugar cane juice and urea) as substrates.…”
Section: Introductionmentioning
confidence: 99%